Wiersz "Do przyjaciółki" ze zbioru "Carmina Rivipullensia" – głos w dyskusji o przekładach średniowiecznej poezji łacińskiej - Woźniak, Maria Judyta (Collectanea Philologica, 2022)
The article is a voice in the discussion on contemporary translations of medieval Latin poetry: accepted and possible ways of translating Latin poetry for todayʼs readers, situated within the field of translation studies and poetics – it is part of the research on the reception of the ancient tradition, of which translations are a particular manifestation. The subject of interest is a poem from the medieval collection Carmina Rivipullensia: the only existing collection of Latin love lyric of the Middle Ages from Spain. It testifies to the very lively presence of the Latin poetic tradition in the Iberian Peninsula at that time. This article presents a translatorʼs proposal, accompanied by a commentary, in which arguments for the chosen solutions are indicated. The aim of the article is to present the translatorʼs ideas, mainly concerning the chosen strategy for the translation of the rhymes in Latin medieval poetry, which are an important feature of the Songs.